Improving adolescent knowledge of emergency contraception: challenges and solutions - Seetharaman S; Yen S; Ammerman SD (Dove Medical Press, 2016)
Sujatha Seetharaman, Sophia Yen, Seth D Ammerman Division of Adolescent Medicine, Stanford University Medical Center, Palo Alto, CA, USA Abstract: Globally, unintended adolescent pregnancies pose a significant burden. One of the most important tools that can help prevent unintended pregnancy is the timely use of emergency contraception (EC), which in turn will decrease the need for abortions and complications related to adolescent pregnancies. Indications for the use of EC include unprotected sexual intercourse, contraceptive failure, or sexual assault. Use of EC is recommended within 120 hours, though is most effective if used as soon as possible after unprotected sex. To use EC, adolescents need to be equipped with knowledge about the various EC methods, and how and where EC can be accessed. Great variability in the knowledge and use of EC around the world exists, which is a major barrier to its use. The aims of this paper were to 1) provide a brief overview of EC, 2) discuss key social determinants affecting knowledge and use of EC, and 3) explore best practices for overcoming the barriers of lack of knowledge, use, and access of EC. Keywords: emergency contraception, adolescents, unintended pregnancy, unprotected sexual intercourse